Landau-Kolmogorov problem for a class of functions absolutely monotone on a finite interval - Skorokhodov, D. S. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We solve the Landau - Kolmogorov problem for the class of functions absolutely monotone on a finite interval. For this class of functions, a new exact additive inequalities of the Kolmogorov type are obtained.